Mitigating Security Threats for Digital Twin Platform: A Systematic Review with Future Scope and Research Challenges - Lipsa, Swati; Dash, Ranjan Kumar; Cengiz, Korhan (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2024)
In Industry 4.0, the digital twin (DT) enables users to simulate future states and configurations for prediction, optimization, and estimation. Although the potential of digital twin technology has been demonstrated by its proliferation in traditional industrial sectors, including construction, manufacturing, transportation, supply chain, healthcare, and agriculture, the risks involved with their integration have frequently been overlooked. Moreover, as a digital approach, it is intuitive to believe it is susceptible to adversarial attacks. This issue necessitates research into the multitude of attacks that the digital twin may face. This study enumerates various probable operation-specific attacks against digital twin platforms. Also, a comprehensive review of different existing techniques has been carried out to combat these attacks. A comparison of these strategies is provided to shed light on their efficacy against various attacks. Finally, future directions and research issues are highlighted that will help researchers expand the digital twin platform.